Proses Transmisi Musik Keroncong Di Yayasan Keroncong Indonesia - Adimas Akma Danish Azfar; Agus Cahyono; Muh Fakhrihun Naam (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Keroncong music is one of Indonesia’s intangible cultural heritages that possesses significant historical, cultural, and aesthetic value; however, its sustainability is currently facing serious challenges amid globalization and shifting preferences among younger generations. A central issue lies in the disruption of regeneration processes, caused by the weakness of transmission mechanisms that are able to bridge tradition with contemporary life contexts. This study aims to examine the learning and transmission processes of keroncong music developed by Maestro Sundari Soekotjo at the Indonesian Keroncong Foundation (Yayasan Keroncong Indonesia, YAKIN) as a strategic model for keroncong conservation through education. The research employs a qualitative approach using a case study design. Data were collected through observation, documentation, and literature review, and were analyzed interactively through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that the keroncong transmission process at YAKIN implements contextual learning structured into four main stages: demonstration through modelling, meaning making through inquiry, discussion based on constructivism, and reflection accompanied by authentic assessment. This learning model not only emphasizes the acquisition of musical technical skills, but also encourages students to collectively construct historical, social, and cultural understandings of keroncong. The study concludes that the contextual learning approach implemented by Maestro Sundari Soekotjo plays an effective role in shaping younger generations as agents of preservation, while simultaneously serving as a conservation mechanism that sustains keroncong music as a living cultural heritage Keyword: keroncong; contextual learning, transmision, conservation, art education Abstrak Musik keroncong merupakan salah satu warisan budaya tak benda Indonesia yang memiliki nilai historis, kultural, dan estetis yang tinggi, namun keberlangsungannya menghadapi tantangan serius di tengah arus globalisasi dan perubahan preferensi generasi muda. Permasalahan utama yang dihadapi adalah terputusnya proses regenerasi akibat lemahnya mekanisme transmisi yang mampu menjembatani tradisi dengan konteks kehidupan kontemporer. Penelitian ini bertujuan untuk mengkaji proses pembelajaran dan transmisi musik keroncong yang dikembangkan oleh Maestro Sundari Soekotjo di Yayasan Keroncong Indonesia (YAKIN) sebagai model strategis dalam upaya konservasi keroncong melalui pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data diperoleh melalui observasi, dokumentasi, serta telaah literatur, kemudian dianalisis secara interaktif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa proses transmisi musik keroncong di YAKIN menerapkan pembelajaran kontekstual dan terstruktur dalam empat tahapan utama, yaitu pemeragaan melalui modelling, pemaknaan melalui inquiry, diskusi berbasis konstruktivisme, serta refleksi yang disertai penilaian autentik. Model pembelajaran ini tidak hanya menekankan penguasaan teknik musikal, tetapi juga mendorong peserta didik untuk membangun pemahaman historis, sosial, dan kultural keroncong secara kolektif. Simpulan penelitian menegaskan bahwa pembelajaran kontekstual yang diterapkan oleh Maestro Sundari Soekotjo berperan efektif dalam membentuk generasi muda sebagai agen pelestarian, sekaligus menjadi mekanisme konservasi yang mampu menjaga keberlanjutan musik keroncong sebagai warisan budaya yang hidup Kata kunci: keroncong; pembelajaran kontekstual, transmisi, konservasi, pendidikan seni